“Cough was Extremely Excruciating”: A Qualitative Study of Pre-Diagnosis Experience among Individuals with Tuberculosis in Samarinda, Indonesia - Khumaidi Khumaidi; Bahtiar Bahtiar (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2024)
Tuberculosis (TB) is a global public health challenge. It's critical to comprehend how an infected person lives with the disease for TB control initiatives to be successful. Identifying the experiences before being diagnosed with tuberculosis needs to be done. This study aimed to explore the pre-experiences among individual that survive from TB. The qualitative method of descriptive phenomenology was utilized in this study. Purposive sampling was used in the sample process, and 16 tuberculosis survivors were included. This study found two themes that were pre-diagnosis symptoms (cough symptom, nutrition problem, hyperthermia and breathing problem) and health seeking behavior prior to being diagnosed with tuberculosis (visit health services, treatment behavior and ignore the symptoms felt). This study revealed that some individuals were still unable to identify the signs of tuberculosis and seek inappropriate treatment before receiving a diagnosis. Particularly for those who are at high risk, interventions aimed at enhancing the community's capacity to identify tuberculosis symptoms and adopt appropriate treatment-seeking behavior must be refined and implemented.